Revisiting the Factor Structure of the German WISC-V for Clinical Interpretability: An Exploratory and Confirmatory Approach on the 10 Primary Subtests - Pauls, Franz; Daseking, Monika (Frontiers in Psychology, 2021)
With the exception of a recently published study and the analyses provided in the test manual, structural validity is mostly uninvestigated for the German version of the Wechsler Intelligence Scale for Children – Fifth Edition (WISC-V; Wechsler, 2014a, 2017b). Therefore, the main aim of the present study was to examine the latent structure of the 10 WISC-V primary subtests on a bifurcated extended population-representative German standardization sample (N = 1,646) by conducting both exploratory (EFA, n = 823) and confirmatory (CFA, n = 823) factor analyses on the original data. Since no more than one salient subtest loading could be found on the Fluid Reasoning factor in EFA, results indicated a four-factor rather than a five-factor model solution when the extraction of more than two suggested factors was forced. Likewise, a bifactor model with four group factors was found to be slightly superior in CFA. Variance estimation from both EFA and CFA revealed that the general factor dominantly accounted for most of the subtest variance and construct reliability estimates further supported interpretability of the Full Scale Intelligence Quotient (FSIQ). In both EFA and CFA, most group factors explained rather small proportions of common subtest variance and produced low construct replicability estimates, suggesting that the WISC-V primary indexes were of lower interpretive value and should be evaluated with caution. Clinical interpretation should thus be primarily based on the FSIQ and include a comprehensive analysis of the cognitive profile derived from the WISC-V primary indexes rather than analyses of each single primary index.